PILIHAN BAHASA ORANG YABEN DI PAPUA BARAT:TINJAUAN DARI HIERARKI KEBUTUHAN MASLOW - Katubi Katubi (Jurnal Masyarakat dan Budaya, 2009)
This paper is an attempt to describe the result of study on Yabenese language choice, in Konda and Wamargege villages, Teminabuan district, South Sorong regency, West Papua province. It is estimated that the speakers of Yabenese language remain 500 left. As a result of language contact with various ethnic groups, Papua Malay language, and Indonesian language, Yabenese people are faced with the problem of language choice in the various fields. The result of analysis of language choice indicates that there is language shift to Papua Malay language. Speakers of Yabenese language from child and teenage groups do not make use of Yabenese language any longer in domestic field. Meanwhile, the teenage group has only a passive command over their ethnic language. The result of analysis on the basis of Maslow’s need hierarchy shows that to meet all the levels of human’s need, Yabenese people need to use another second language with wider coverage. Fulfillment of the need, specifically physiological need, in this study is considered the impetus of the occurence of Yabenese language shift. Keywords: Yaben, language choice, Maslow’s need hierarchy